Relationship Between Bi-Caudate Ratio and White Matter Atrophy in Brain MRI of Multiple Sclerosis - Hussein Soleimantabar; Shno Hosseini (Novelty in Biomedicine)
Background: Multiple sclerosis (MS) is one of the most common and debilitating neurological diseases. Brain magnetic resonance imaging (MRI) is critical to determine the prognosis of MS. Using simple and accessible techniques is one of the researchers' concerns. So far, limited studies have been conducted on evaluating the relationship between the Bi-caudate ratio (BCR) and white matter atrophy in brain MRI of patients with MS. Therefore, in this study, we decided to evaluate this relationship.